МЕТОДОЛОГІЧНІ АСПЕКТИ ДОСЛІДЖЕНЬ АНГЛОМОВНИХ КОМПАРАТИВІСТІВ - Артемій Теодорович (Pavlo Tychyna Uman State Pedagogical University, 2015)
Вагомий внесок науковців англомовного світу у розвиток методологічних засад компаративістики засвідчує актуальність їхніх праць  для сучасних українських та зарубіжних освітян-міжнародників. У статті зроблено спробу огляду порівняльно-педагогічних досліджень, оприлюднених у 70-х та 80-х роках ХХ століття у різних спеціалізованих англомовних виданнях.  Автор окреслює перспективи досліджень, покликаних виявити тенденції відповідних розробок в Україні. В статье изложена попытка осуществить обзор сравнительно-педагогических трудов, опубликованых в 1976-1986 гг. в разных англоязычных изданиях. О весомом вкладе учёных англоязычного мира данного периода в развитие методологических начал отрасли свидетельствует актуальность их исследований как для современных педагогических работников стран Запада, так и для их украинских колег. Автор очерчивает перспективы сравнительно-педагогических исследований, призванных выявить тенденции развития отрасли в Украине. The scientific works of specialized editions, published in 1976-1986 in major English-speaking countries are reviewed in the article. Their importance is traced to modern research currents in the field, both in Ukraine and abroad. The author outlines some prospects of future research, directed onto rising tendencies of Ukrainian comparative education. The journals of any arising science has been very important for establishing the field. The editorial boards as well as the authors of these specialized periodicals are called to become generators of new tendencies and then, constantly revising them elaborate the generally recognized methodologies. It is fully illustrated in the history of the Comparative Education Review (CER) activity. Since its first decades one of the most influential journals of the field published the articles reviewing and generalizing its materials. English-speaking materials of the professional journals and other comparative education works is not an exhausting source for analyzing the world tendencies of the field, although a small number of respective publications of 1970s and 1980s, and the fact that authors of the Review, "Compare: A Journal of Comparative Education", "Canadian and International Education" and some other English-speaking editions gave possibilities to distinguish general tendencies of the field development with the great degree of authenticity. Therefore the retrospective analysis of Philip G. Altbach & Gail P. Kelly article "Comparative Education: Challenge and Response"(CER, Vol.30, No.1, 1986) will reflect the contents and dynamics of the world currents in the field at that time, and in many cases find the sources for issues of concern for modern comparativists both in Ukraine and abroad. In particular the issues of 'structural functionalism' methodology critics, gender, and units of comparison are still the subjects of numerous research of the field. Taking into account the great volume of works of Ukrainian authors both on the topics mentioned above and others the necessity of their conclusions thorough analysis is evident to define the respective tendencies of the research in Ukraine and elaborate forecasts for the future as well.